Performance Analysis of PT PNM Tangerang Branch Using Balanced Scorecard - Simare Mare, Eben; Suharto, Eduardus (Educational Studies and Research Journal, 2025)
This study analyzes the performance of PT PNM Tangerang Branch using the Balanced Scorecard method across four perspectives: financial, customer, internal business processes, and learning and growth. A quantitative approach was employed, utilizing both primary and secondary data. Primary data were collected from employees and customers of PT PNM Tangerang Branch through surveys, while secondary data were obtained from financial reports, relevant books, journals, and previous studies. The findings reveal that the internal business process perspective performs well, though improvement is needed in the dissemination of financing programs. The customer perspective demonstrates satisfactory performance. The learning and growth perspective shows positive results, but employee workload requires evaluation due to the perceived high burden. However, the financial perspective indicates poor performance, as the company has failed to generate profit for three consecutive years, primarily due to high operational costs. These results suggest that while non-financial dimensions are relatively strong, financial sustainability requires immediate strategic intervention to reduce operational expenses and improve profitability.